Acceptability of mindfulness with National Collegiate Athletic Association Division I student-athletes: a pilot study - Economou, P. J.; McGehee, C.; Torres, C.; Anderson, S.; Sanfilippo, J. (Journal of Clinical Sport Psychology, 2025)
Researchers have found that mindfulness meditation can reduce stress and anxiety, support physical and mental well-being, and reduce risk of injuries for student-athletes. Limited research exists on the utilization of mindfulness-based interventions (MBIs) with National Collegiate Athletic Association Division I student-athletes; no studies on the acceptability of mindfulness with this student-athlete population have been conducted, despite the increased application of MBIs within university settings. The researchers conducted this pilot study to understand whether Division I student-athletes from a Power Five conference (now known as Power Four conferences) found MBIs acceptable. Two-thirds of the sample believed that MBIs were acceptable. This acceptance spanned across sport and gender, although there were no statistically significant differences between groups. Implications from this pilot study call for the consideration of integration of MBIs into the organizational, team, and sport culture and further support the use of MBIs with National Collegiate Athletic Association Division I student-athletes.